Wound healing - characteristics of the ideal dressing - Kinga Orlińska; Katarzyna Komosińska-Vassev; Krystyna Olczyk; Marcin Glaesel; Paweł Olczyk (Śląski Uniwersytet Medyczny w Katowicach, 2023)
Wound healing is a dynamic process aimed at restoring homeostasis and functionality of damaged tissue. It is a highly complex, multi-stage process, the disruption of which leads to complications and health problems for the injured person. The discussed process takes place in the human system in two ways. The first of them is granulation and the second is healing per primary. Regardless of the method of wound healing, the individual phases of this process overlap each other, where before the end of the previous phase, the next begins. Demarcation of individual phases is purely practical. There are four phases of healing: the hemostasis phase, the inflammation phase, the proliferative phase - in other words the replication and synthesis phase - and the remodeling phase. The process of wound healing is a natural, long-term, and complex process that occurs in the body when injured. Incorrect healing may result in chronic wounds, necrosis or excessive scarring. Wound treatment supports this naturally occurring process in the body. In cases that require such support dressings are used, which are an essential element applicable in health care. An ideal dressing should create a barrier against external factors, maintain an appropriate environment in the wound bed (appropriate temperature, optimal humidity, slightly acidic pH, gas exchange), absorb excess of blood and exudate, keep the wound clean - cleanse it of necrotic tissue and toxins - do not adhere to the wound to avoid wound damage during dressing replacement, do not show sensitizing or irritating effects.